Lighting direction and visual field modulate perceived intensity of illumination - McCourt, Mark E.; Blakeslee, Barbara; Padmanabhan, Ganesh (Frontiers in Psychology, 2013)
When interpreting object shape from shading the visual system exhibits a strong bias that illumination comes from above and slightly from the left. We asked whether such biases in the perceived direction of illumination might also influence its perceived intensity. Arrays of nine cubes were stereoscopically rendered where individual cubes varied in their 3D pose, but possessed identical triplets of visible faces. Arrays were virtually illuminated from one of four directions: Above-Left, Above-Right, Below-Left, and Below-Right (±24.4o azimuth; ±90o elevation). Illumination intensity possessed 15 levels, resulting in mean cube array luminances ranging from 1.31-3.45 cd/m2. A “reference” array was consistently illuminated from Above-Left at mid-intensity (mean array luminance = 2.38 cd/m2). The reference array’s illumination was compared to that of matching arrays which were illuminated from all four directions at all intensities. Reference and matching arrays appeared in the left and right visual field, respectively, or vice versa. Subjects judged which cube array appeared to be under more intense illumination. Using the method of constant stimuli we determined the illumination level of matching arrays required to establish subjective equality with the reference array as a function of matching cube visual field, illumination elevation, and illumination azimuth. Cube arrays appeared significantly more intensely illuminated when they were situated in the left visual field (p = .017), and when they were illuminated from below (p = .001), and from the left (p = .001). An interaction of modest strength was that the effect of illumination azimuth was greater for matching arrays situated in the left visual field (p = .042). We propose that objects lit from below appear more intensely illuminated than identical objects lit from above due to long-term adaptation to downward lighting. The amplification of perceived intensity of illumination for stimuli situated in the left vis